Acute Angiographic and Intermediate-Term Clinical Results of Patients with Non-Left Main Coronary Bifurcation Lesions Treated with BVS by Jailed Semi-Inflated Balloon Technique and Provisional Side-Branch Stenting Strategy - Chieh-Shou Su; Keng-Hao Chang; Chih-Hung Lai; Yu-Wei Chen; Tzu-Hsiang Lin; Hung-Chih Pan; Tsun-Jui Liu; Wen-Lieng Lee (Journal of Interventional Cardiology)
Background. To evaluate the acute angiographic and intermediate-term clinical results of patients with non-left main (LM) coronary artery bifurcation disease (CABD) treated with BVS, as compared with those treated with DES, using the jailed semi-inflated balloon technique (JSIBT) for side branch (SB) protection and provisional stenting. Methods and Results. Sixty-eight patients with non-LM CABD who had undergone provisional one-stent implantation with SB protection by JSIBT between January 2015 and December 2017 were retrospectively enrolled. Among them, 20 patients received Absorb BVS implantation and 48 patients received DES implantation. Patients in the BVS group were younger and had higher BMI, total cholesterol, low-density lipoprotein cholesterol, and hemoglobin but had lower serum creatinine and lower prevalence of prior PCI and MI. No SB balloon rupture/entrapment occurred in either group. The incidence of SB dissection/occlusion and SB in need of rewiring or stenting was rare in both groups and showed no significant difference between them. Postinterventional TIMI flow significantly increased in both groups. The intermediate-term clinical outcomes were good in terms of incidence of target lesion failure, target lesion revascularization, target vessel revascularization, myocardial infarction, and all-cause death in both groups. Conclusion. The use of JSIBT for treating CABD with modern BVS can provide SB protection as similar as those with DES, even with higher incidence of acute SB dissection/occlusion. The immediate angiographic results and acute and intermediate-term clinical outcomes were also similar in both groups. Our study results demonstrate that JSIBT might be a safe and alternative SB protection tool for BVS in patients with complex CABD.